0=-2(y+3)

Simple and best practice solution for 0=-2(y+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=-2(y+3) equation:


Simplifying
0 = -2(y + 3)

Reorder the terms:
0 = -2(3 + y)
0 = (3 * -2 + y * -2)
0 = (-6 + -2y)

Solving
0 = -6 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
0 + 2y = -6 + -2y + 2y
Remove the zero:
2y = -6 + -2y + 2y

Combine like terms: -2y + 2y = 0
2y = -6 + 0
2y = -6

Divide each side by '2'.
y = -3

Simplifying
y = -3

See similar equations:

| 4x+2x+3=3x+x+7 | | 3x^2+33x+84= | | 5+(2x-3)=x-(3x+10) | | 26+x=(-4) | | 2v-2=-6 | | 4x-3=-29 | | 3.5=4-3x | | x^4-6x^2-7x-6=0 | | s+9=4 | | 5x-5=x+15 | | 5=3b | | 9x-18=3x | | 7(8n+12)=7(1+6n)+7 | | 5x-15=25 | | 8+4x=24 | | 106-76=28y-34y | | 3-4y=8 | | 6x+9=21 | | -6x-9=-45+6x | | 2x-4=3x | | 7-3(2x-5)=1-x | | -15=4-3x | | -4x+6=-3x-4 | | 3x-4y=8 | | 2x^3-x^2+2x+5=0 | | 8.2x+13=1.4x+19.8 | | 6+3x=27 | | 5(x+1)=-7(3-1) | | -540=-20(-3b) | | 21=4-3x | | 0=x^2+15x+-236 | | -2x=-2+2x |

Equations solver categories